Peshawar School Massacre, Pakistan: A Qualitative Account of Citizens’ Perceptions - Fatima Asim; Muhammad Bilal (Journal of Political Studies, 2017)
On 16th December 2014, Army Public School and College (APSAC), Warsak road, Peshawar, located in the Khyber Pakhtunkhwa Province of Pakistan, was attacked by more than six militants dressed as Pakistan Army Soldiers which resulted in killing of 149 people, mostly innocent children. After this attack, Government with the collaboration of Military took immediate steps for the eradication of terrorists from Pakistan and announced National Action Plan (NAP). Based on Master’s Fieldwork in Rawalpindi city, this study explores peoples’ reasoning to why such an attack took place? The paper further investigates whether the citizens of Rawalpindi are satisfied with the counter-terrorism steps taken immediately after the Peshawar incident. The locale of the study was Rawalpindi’s Union Council number 30. This qualitative study used purposive sampling techniques to draw a heterogeneous sample of 31 participants in order to conduct In-depth interviews